Thyroxine and thyroid stimulating hormone levels in under-five severe malnourished children - Shelvi H. Tamzil; Ryadi Fadil; Diet S. Rustama; Melinda D. Nataprawira (Paediatrica Indonesiana, 2003)
Background In Indonesia, protein energy malnutrition (PEM) inchildren is still a health problem. Malnourished children will havegrowth and development disruption, which is not only caused bynutritional factor, but might be associated with endocrine system,such as thyroid hormone metabolism. Hypothyroidism or thyroidhypofunction could be happened in malnourished children.Objective The purpose of this study was to assess thyroxine (T4)and thyroid stimulating hormone (TSH) levels in under-five severemalnourished children.Methods This was a descriptive study with cross sectional design.Subjects were all under-five severe malnourished childrenbased on nutritional evaluation in August 2001 done by local healthcare workers in Andir District, Bandung. Severe malnutrition wasdefined as weight for age less than -3SD (W/A <-3SD).Results There were 42 subjects who fulfilled inclusion criteria, aged11-57 months, five of them showed clinical manifestation of marasmus.The T4 levels of the 41 subjects were still in normal limitsand within the range of 4.5-11.2 mg/dl. Thirty-nine subjects hadnormal TSH levels, ranged from 0.9 to 5.0 mlU/ml, and 2 subjectsshowed increased TSH levels of 6.8 and 7.6 mlU/ml, respectively.Reduced T4 and TSH levels of 3.93 mg/dl and 0.2 mlU/ml, respectivelywere detected in one subjectConclusion In general, the T4 & TSH levels were still normal,with only one subject (2%) showed low levels of T4 & TSH.